A comparative evaluation of bifidobacteria levels in early childhood caries and severe early childhood caries - Suraj Nair; V Suresh Kumar; Ramesh Krishnan; Pooja Rajan (Wolters Kluwer Medknow Publications, 2017)
Background: Bifidobacteria levels in saliva were found to be significantly correlated in adults with dental caries but less information available in the literature regarding its role in children. Aim: The aim is to compare the salivary levels of Bifidobacteria in children who are caries free with that of early childhood caries (ECC) and severe ECC (S-ECC). Materials and Methods: Saliva was collected using the tongue-loop method from a total of 60 children between the age group of 3-5 years and they were further divided into 3 groups. In addition, the age and gender of the children, sugar amount in diet, sugar frequency in diet, were recorded. Results: Bifidobacteria was isolated from all the three groups, but more were from S-ECC, followed by ECC and very few cases of caries-free children and was found to statistically significant (P < 0.001). Salivary levels of Bifidobacteria were significantly correlated with amount of sugar in the diet and frequency of sugar consumption. Conclusions: Salivary levels of Bifidobacteria were significantly associated with S-ECC and ECC, followed by caries free group. In future, it can be used as a salivary marker for caries risk assesment.